Redescription of the rare and endangered Broadfin Shark Lamiopsis temminckii (Müller & Henle, 1839) (Carcharhiniformes:Carcharhinidae) from the northeastern Arabian Sea - Akhilesh, K.v.; White, W.t.; Bineesh, K.k.; Purushottama, G.b.; Singh, V.v.; Singh, V.v.; Zacharia, P.u. (Zootaxa, 2016)
The genus Lamiopsis (Carcharhinidae) was previously considered to be monotypic, containing only the Broadfin Shark Lamiopsis temminckii (Müller & Henle, 1839) widely distributed in the Indo–West Pacific. However, a recent taxonomic study revealed that the Western Central Pacific populations were a separate species and that L. temminckii was restricted to the northern Indian Ocean. In this study, the paucity of data available for the true L. temminckii was highlighted. Recently collected specimens of L. temminckii has allowed for a detailed redescription of this species from the northern Arabian Sea to complement the previous taxonomic work on this genus.